Inefficiency and Gaps in Financial Stability in sub-Saharan Africa - Evans Kulu; William Gabriel Brafu-Insaidoo; Eric Amoo Bondzie; James Atta Peprah (Cogent Economics & Finance, 2022)
Using the Stochastic Frontier Analysis on data for 33 sub-Saharan African countries over the period 2007 to 2018, we determine the drivers of the inefficiencies in financial stability and also estimate the existing financial stability gaps. The results confirm that credit to the private sector and the level of unemployment are significant drivers of financial stability in SSA, while employment, domestic savings, and regulatory quality significantly decrease the inefficiencies in financial stability. Further, it is revealed that government domestic debt arrears promote financial stability inefficiencies in SSA. Countries within the East Africa Community Countries (EAC) have the highest mean efficiency and the least financial stability gap for the period studied. It is therefore recommended that government borrowing from the domestic economy should be towards projects that have undergone proper appraisal as a means to reduce arrears accumulation. Employment is recommended to improve income while encouraging domestic savings as a conscious effort to enable the financial sector to perform its intended essential role in the economy.
Keywords: 330; financial stability; government domestic debt; gap; stochastic frontier analysis